2021
DOI: 10.1016/j.soilbio.2021.108420
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial community structure and putative nitrogen-cycling functional traits along a charosphere gradient under waterlogged conditions

Abstract: Unique spatial niches created by biochar form a dynamic biogeochemical soil zone, termed the "charosphere". Charosphere soil has different properties from either soil or biochar, often acting as a hotspot for microbial activity. However, the direction and magnitude of charosphere effects on soil processes and microbial communities remain inconclusive. Herein, we designed a multi-sectional box to separate charosphere soils from biochar under waterlogged conditions, investigating millimeter-scale changes in bact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(4 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…Previous studies reported that MND1 played a pivotal role in soil nitrogen cycling [86]. RB41 exhibited the remarkable ability to selectively regulate the decomposition of soil organic matter and the carbon cycling process in agricultural soils and positively correlated with soil pH [87][88][89]. We believe that this is the reason that certain bacteria have evolved effective strategies to thrive in extreme environments.…”
Section: The Main Drivers Of Bacteria Community In the Soil Character...mentioning
confidence: 81%
“…Previous studies reported that MND1 played a pivotal role in soil nitrogen cycling [86]. RB41 exhibited the remarkable ability to selectively regulate the decomposition of soil organic matter and the carbon cycling process in agricultural soils and positively correlated with soil pH [87][88][89]. We believe that this is the reason that certain bacteria have evolved effective strategies to thrive in extreme environments.…”
Section: The Main Drivers Of Bacteria Community In the Soil Character...mentioning
confidence: 81%
“…The composition of AOB is quite similar with Nitrosomonas being the key genera in both samples (Figure 5c,d). Other shared bacteria include the uncultured genus Ellin6067 and MND1, belonging to the family Nitrosomonadaceae are also of note and are both involved in NH 4 + oxidation processes (Wang et al, 2021; Yu et al, 2021). Chloroflexi here identified at the phylum level was only found in the PAD's test B biomass sample (Figure 5c); this phylum has been often found associated with thermophilic environment and with NH 4 + oxidation (Herber et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Bradyrhizobium has a symbiotic relationship with leguminous plants and participates in nitrogen fixation ( 56 ). Gemmatimonadaceae and Sphingomonas are known plant-promoting microorganisms, which can dissolve phosphorus, sulfur, and calcium and produce a variety of plant hormones and iron carriers ( 57 , 58 ). Changes in Sphingomonas , a rhizosphere biomarker, could prove that the poplar rhizosphere provides sufficient air and organic nutrient conditions for these microorganisms ( 57 ).…”
Section: Discussionmentioning
confidence: 99%
“…Gemmatimonadaceae and Sphingomonas are known plant-promoting microorganisms, which can dissolve phosphorus, sulfur, and calcium and produce a variety of plant hormones and iron carriers ( 57 , 58 ). Changes in Sphingomonas , a rhizosphere biomarker, could prove that the poplar rhizosphere provides sufficient air and organic nutrient conditions for these microorganisms ( 57 ). It has been demonstrated that microbial communities isolated from Populus can enhance the health, growth, and development of plant hosts ( 43 , 46 ).…”
Section: Discussionmentioning
confidence: 99%